1994
DOI: 10.1002/cne.903400409
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐eye barriers in the rat: Correlation of ultrastructure with function

Abstract: The function of different vascular beds in the rat eye and brain was evaluated by measuring the transfer of a vascular tracer, 14C-alpha-amino-isobutyric acid, from blood to tissue. The density of vascular pores was measured in electron micrographs of perfusion-fixed, age-matched tissue to determine whether the differences in tracer transfer were paralleled by differences in ultrastructure. Tracer transfer in retina was approximately four times that in brain of the same animal. The transfer constant was not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 40 publications
(41 reference statements)
4
72
0
Order By: Relevance
“…It is speculated that RhIc had readily gained access into the retinal tissues by direct and massive diffusion rather than active transendothelial transportation as was reported in the brain (Xu et al 1993). This is supported by the study of Stewart & Tuor (1994), who demonstrated that the blood-retina barrier (BRB) was 4 times more permeable than the blood-brain barrier (BBB) by measuring the transfer of a vascular tracer, "%C-AIB from blood to tissue ; a similar phenomenon was also reported by other authors (Alm & Tornquist, 1981 ;Ennis & Betz, 1986). It is suggested that the extravasated RhIc in the retinal tissues was readily endocytosed by the resident microglia.…”
Section: Labelled Microglia In the Retina Of 7-d-old Rats Killed At Dsupporting
confidence: 59%
“…It is speculated that RhIc had readily gained access into the retinal tissues by direct and massive diffusion rather than active transendothelial transportation as was reported in the brain (Xu et al 1993). This is supported by the study of Stewart & Tuor (1994), who demonstrated that the blood-retina barrier (BRB) was 4 times more permeable than the blood-brain barrier (BBB) by measuring the transfer of a vascular tracer, "%C-AIB from blood to tissue ; a similar phenomenon was also reported by other authors (Alm & Tornquist, 1981 ;Ennis & Betz, 1986). It is suggested that the extravasated RhIc in the retinal tissues was readily endocytosed by the resident microglia.…”
Section: Labelled Microglia In the Retina Of 7-d-old Rats Killed At Dsupporting
confidence: 59%
“…Vesicular profiles are very common in somatic capillaries (Simionescu & Simionescu, 1984 ;Simionescu et al 1985). By contrast, these structures are relatively sparse in capillaries of brain and retina (Stewart & Tuor, 1994), suggesting that under . Similarly Allo A labelling of brain microvessels is weak (c) but after neuraminidase treatment is strong (d).…”
Section: mentioning
confidence: 99%
“…For the therapeutic treatment of most of ocular problems, topical administration undoubtedly seems preferred mode, because for systemically administered drugs, only a very small fraction of the total dose will reach the eye from the general circulatory system. Even distribution for this fraction to the inside of the eye is further hindered by the blood-retinal barrier (BRB), which is almost as effective as blood-brain barrier (BBB) in restricting the passage of xenobiotics from the blood stream [34]. Therefore despite its apparent accessibility, the eye, in fact, is well protected against the absorption of foreign materials, including drug molecules, by the eyelids, by flow of tears, and also by the permeability barriers imposed by the cornea on one side and the blood-retinal barrier on the other side as mentioned above [24].…”
Section: Eye-targeted Chemical Delivery Systems (Cdss) and Retrometabmentioning
confidence: 99%
“…From the various soft -blockers developed along these lines by Bodor and Buchwald [24], Adaprolol (33), an adamantane ethyl ester was selected as a potential candidate for a new topical antiglaucoma agent [24 ]. The metabolism of the well-known  -blocker Metoprolol (34) has been compared with that of the soft  -blocker Adaprolol which has been designed starting from one of Metoprolol`s inactive acid metabolite (35), viz., phenyl acetic acid (Figure 4). Its other metabolites include -hydroxymetoprolol (36) and ODimethylmetoprolol (37) both of which are active.…”
Section: Soft--blockersmentioning
confidence: 99%
See 1 more Smart Citation